Association Rule Mining and Data Mining (IntechOpen, 2026)
This book discusses the recent advances and applications of association rule mining techniques in data mining tasks. Association Rule Mining is an emerging and interdisciplinary field of research in data mining. It draws on ideas from various fields to extract association rules or patterns from large databases. Researchers and companies frequently use the concepts of association rule and data mining for prediction/classification tasks. In today’s digital era, vast amounts of data are being generated and stored in databases. Therefore, there is a need to analyze the data and identify important association rules and patterns from this vast dataset. Recent Advances in Association Rule Mining and Data Mining is an important step in this direction. The primary aim of the book is to provide the reader with a comprehensive overview of recent advances and developments in this field. The book is a collection of reviewed book chapters written by researchers, academicians, and other research scientists working in the areas of Association Rule Mining and Data Mining.